2015
DOI: 10.1016/j.atherosclerosis.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between carotid intima-media thickness and carotid plaque in the Northern Manhattan Study

Abstract: Objective Carotid intima–media thickness (cIMT) and carotid plaque (CP) are proposed biomarkers of subclinical atherosclerosis associated with stroke risk. Whether cIMT and CP are distinct phenotypes or single traits at different stages of atherosclerotic development is unclear. We explored the relationship between these markers in the population-based Northern Manhattan Study. Methods We used high-resolution ultrasound and validated imaging protocols to study the cross-sectional (N=1,788 stroke-free partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 43 publications
2
43
0
2
Order By: Relevance
“…We did not find associations with other traditional risk factors such as systolic blood pressure, race, and sex. 27–31 A few possibilities may account for these findings. This sample comprised predominantly young ethnic and racial minority participants in whom elevated blood pressure may not have yet manifested.…”
Section: Discussionmentioning
confidence: 99%
“…We did not find associations with other traditional risk factors such as systolic blood pressure, race, and sex. 27–31 A few possibilities may account for these findings. This sample comprised predominantly young ethnic and racial minority participants in whom elevated blood pressure may not have yet manifested.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of plaque was defined as a focal wall thickening or protrusion in the lumen more than 50% greater than the surrounding thickness. 19 cIMT was measured in areas without plaque and calculated as a composite measure of the near and the far walls of the CCA, bifurcation, and internal carotid artery (ICA) intima media thickness (IMT) of both sides of the neck, and expressed as a mean of the maximum measurements of the 12 carotid sites. We also examined IMT in the bifurcation and ICA exclusively and IMT in the CCA exclusively.…”
Section: Methods Study Population the Northern Manhattanmentioning
confidence: 99%
“…We also examined IMT in the bifurcation and ICA exclusively and IMT in the CCA exclusively. 19 Beta stiffness index was calculated as a ratio between natural log transformation of systolic blood pressure (SBP) 2 diastolic blood pressure (DBP) over STRAIN (ln[SBP 2 DBP]/STRAIN), where STRAIN was expressed as (systolic diameter 2 DD)/DD. 20 Blood pressure was measured in the right arm using a Dinamap Pro100 (Critikon Inc., Tampa, FL) automatic sphygmomanometer after the participants had rested for 10 minutes in a supine position.…”
Section: Methods Study Population the Northern Manhattanmentioning
confidence: 99%
“…Carotid intima‐media thickening (CIMT) and carotid plaque (CP) are considered to be surrogate subclinical markers of early atherosclerosis, are associated with stroke risk (Georgios et al., 2006; Rundek et al., 2015), and can predict the occurrence of ischemic cerebrovascular events (Prati et al., 2008). There is a study that found that increased common carotid artery stiffness is associated with ischemic stroke (Tsivgoulis et al., 2006).…”
Section: Introductionmentioning
confidence: 99%